The Analysis of the Labor Market in Albania - SINAJ, Zamira (European Journal of Economics and Business Studies, 2017)
Albania’s economic growth after 1990 was among the highest of all the economies in transition. Economic activity, as measured at the fair value of the gross domestic product (GDP) for the period 1996-2015 grew at an average annual rate of 5.6 percent, despite the shock of 1997 because of the collapse of the pyramid schemes and the contraction in GDP growth in 20014-2015 due to the impact of the economic and financial crisis. Such high levels of economic growth, has been preceded by economic and structural reforms and the expansion of services and construction, spurred by remittances and informal activities.